Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.cis.2020.102118
|View full text |Cite
|
Sign up to set email alerts
|

Design and use of model membranes to study biomolecular interactions using complementary surface-sensitive techniques

Abstract: Highlights• Model biomembranes at surfaces are useful to study biomolecular interactions • The model membrane complexity can be adapted from one to multiple components • Implementations range from lipid monolayers to a range of supported bilayers • Complementary surface-sensitive techniques allow studying model membranes • Information accessible is reviewed via the use of the peptide Melittin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 207 publications
1
83
0
1
Order By: Relevance
“…NR also allows to simultaneously resolve potential lipid removal as well as peptide insertion into partly deuterated supported lipid bilayers (SLBs). [31][32][33][34][35][36][37][38] In an earlier work, we showed that NR results can be directly compared to results from detailed modelling of small angle X-ray scattering (SAXS) data on monomeric peptide lipid bilayer using SLBs or unilamellar vesicles respectively. 31 For supramolecular nanobers in particular, NR has an advantage over bulk methods since it lacks 3D orientation averaging and enables precise structural determination of complex MDP-membrane structures.…”
Section: Introductionmentioning
confidence: 99%
“…NR also allows to simultaneously resolve potential lipid removal as well as peptide insertion into partly deuterated supported lipid bilayers (SLBs). [31][32][33][34][35][36][37][38] In an earlier work, we showed that NR results can be directly compared to results from detailed modelling of small angle X-ray scattering (SAXS) data on monomeric peptide lipid bilayer using SLBs or unilamellar vesicles respectively. 31 For supramolecular nanobers in particular, NR has an advantage over bulk methods since it lacks 3D orientation averaging and enables precise structural determination of complex MDP-membrane structures.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we firstly employ quantitative single particle microscopy [ 26 , 27 ], and arrays of surface tethered liposomes as model cell membranes [ 28 , 29 ] to observe directly several successive docking events of SL assemblies on individual nanoscale liposomes (see Figure 1 ) and provide a quantitative understanding of how membrane charge and acidic pH may regulate these interactions. Utilizing a biophysical system such as liposomes enables a deconvolution of regulatory effects (i.e., pH and surface charge) as well as the observation of several successive events that remain masked in contemporary measurements and thus provide insights into the underlying mechanism of interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of membrane domains enriched in cholesterol and sphingolipids was also reproduced in biomimetic lipid membranes and resulted in having a strong impact on the interaction with the Aβ peptide [101]. In this context, the characterization by X-ray diffraction of supported lipid membranes made of dimyristoylphosphatidylcholine (DMPC), dimyristoylphosphoserine (DMPS), and cholesterol (at 30 mol%) demonstrated the effect of the membrane lipid composition in modulating the interactions with Aβ(1-42) and Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) fragments [102]. Additional recent studies on Aβ-membrane interaction used vesicles and supported lipid bilayers with a complex lipid composition, including raft lipids such as cholesterol and sphingomyelin (SM), but also polyunsaturated fatty acids (PUFA) (better known as omega-3 lipids), and showed the central role of omega-3 lipids in favoring a deeper internalization of the peptide among the lipid acyl chains and, consequently, hindering its pathogenic self-aggregation [103,104].…”
Section: Protein-lipid Interactionsmentioning
confidence: 92%
“…Indeed, scattering techniques, including neutrons, X-ray, and light as probes, spectroscopy techniques, e.g., fluorescence spectroscopy, NMR, electron paramagnetic resonance (EPR) spectroscopy, and calorimetry are typically used for the investigation of lipid membranes in solution [27][28][29]. On the other hand, surface sensitive techniques such as neutron and X-ray reflectometry and diffraction, Langmuir isotherms, attenuated total reflectance-FTIR, and microscopy techniques, e.g., electron microscopy, fluorescence microscopy, atomic force microscopy, and Brewster angle microscopy, are suitable for the characterization of lipid membranes on surfaces [29,30]. In this section, we discuss the main characteristics of the two types of biomimetic lipid membranes together with a brief description of their respective sample preparation protocols.…”
Section: Design Of Biomimetic Lipid Membranesmentioning
confidence: 99%